2018
DOI: 10.1111/ecc.12903
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between primary and secondary care about patients with cancer: A qualitative mixed-methods analysis

Abstract: Cancer care is complex and involves many different healthcare providers, especially during diagnosis and initial treatment, and it has been reported that both general practitioners and oncology specialists experience difficulties with interdisciplinary communication. The aim of this qualitative study was to explore information sharing between primary and secondary care for patients with lung, breast or colorectal cancer. A qualitative content analysis of 50 medical files (419 documents) was performed, which id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…Compared to a previous study which recruited 248 indigenous cancer patients from hospitals in Queensland, 49 18,19,49 the higher proportion of medical charts at PHC services with missing cancer stage is of concern and it may be attributed to poor communication between hospitals and PHC services. [53][54][55] In a qualitative content analysis of the letters from specialists to GP from 50 patients with lung, breast or colorectal cancer in the Netherlands, while information about cancer treatment was always present, only limited detail was noted about the intent of the treatment (curative vs palliative), treatment alternatives, or about how the patient had reacted to the information received. In other disease groups, both the quality and the availability of HDS in the PHC setting varied.…”
Section: Communication About Cancer In Primary Carementioning
confidence: 99%
See 2 more Smart Citations
“…Compared to a previous study which recruited 248 indigenous cancer patients from hospitals in Queensland, 49 18,19,49 the higher proportion of medical charts at PHC services with missing cancer stage is of concern and it may be attributed to poor communication between hospitals and PHC services. [53][54][55] In a qualitative content analysis of the letters from specialists to GP from 50 patients with lung, breast or colorectal cancer in the Netherlands, while information about cancer treatment was always present, only limited detail was noted about the intent of the treatment (curative vs palliative), treatment alternatives, or about how the patient had reacted to the information received. In other disease groups, both the quality and the availability of HDS in the PHC setting varied.…”
Section: Communication About Cancer In Primary Carementioning
confidence: 99%
“…Comparable data about the quality of HDS in cancer population, and data on tracking HDS from the hospital to the PHC setting, are scarce. 55 A Canadian study reported substantial communication challenges between health professionals involved in cancer care (e.g. In a review of 55 studies, including mixed disease populations and countries, HDS often lacked important information (e.g.…”
Section: Communication About Cancer In Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…The present findings also point to a lack of communication between BC specialists and other professionals, such as GP, OP and social workers, regarding BC survivors' RTW. This is doubtless multifactorial, involving a lack of time on all sides and insufficient training, habits, and value attached to multidisciplinary teamwork beyond cancer treatment (47). While the communication among healthcare professionals for cancer survivor follow-up, as well as the role of communication between occupational health, employers and colleagues to managing RTW has been identified as key in the cancer survivor in the literature (28,37,48,49), the communication between BC specialists and other professionals regarding RTW has not received much attention.…”
Section: Bc Specialists' Working Environment Training and Professiomentioning
confidence: 99%
“…Wij brachten daarom in kaart welke informatie in Nederland wordt uitgewisseld tussen huisartsen en medisch specialisten over patiënten met borst-, long-en darmkanker vanaf verwijzing tot aan het eind van de initiële behandelfase. 7 Hiervoor analyseerden we in een kwalitatief onderzoek 419 documenten uit 50 patiëntendossiers uit drie verschillende ziekenhuizen in Noord-Nederland. Daarnaast interviewden we vier huisartsen, vier medisch specialisten en een verpleegkundig specialist over onderlinge communicatie.…”
unclassified